IMPLEMENTATION OF PEACE-LOVING AND UNITY CHARACTERISTICS IN DOLOKSANGGUL KB STIKES DORMITORY - Pardomuan Simanulang; Jesika Yohana Sitorus; Jeremia Togatorop (Fox Justi : Jurnal Ilmu Hukum, 2023)
Instilling character education from an early age is crucial in preventing violence and riots among students. Parents must make efforts to instill peace-loving values, ensuring that good character traits are ingrained in their children. Love for peace is demonstrated through attitudes, words, and actions that promote happiness, safety, and comfort in others. In line with the third precept of Pancasila, which emphasizes "Indonesian Unity," fostering unity and harmony among students in higher education institutions is vital for creating a peaceful atmosphere. The study conducted at the DolokSanggul KB Stikes Dormitory highlights the effective implementation of peace-loving character education through various means, such as role modeling by dormitory mothers, promoting non-violence, creating a peaceful environment, and employing a learning approach that emphasizes cooperation, tolerance, caring, mutual respect, and empathy. The involvement of leaders or dormitory mothers in student organizations further contributes to fostering peace and harmony. Overall, the cultivation of peace-loving and unity characters in the dormitory has been successfully carried out based on the research findings.